Multistage structure silicon-based CoMn-LDO catalyst and preparation method and application thereof

By thermal activation and surfactant modification of kaolin, Co(Mn)Al-LDH is generated, and a multi-stage structure CoMn-LDO catalyst is prepared after high-temperature calcination, the problem of structure collapse of the CoMn-LDO catalyst under high temperature conditions is solved and the catalytic oxidation performance is improved.

CN119500175APending Publication Date: 2025-02-25CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411638799.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the sheet-like structure of the layered bimetallic hydroxide Co(Mn)Al-LDH is prone to collapse when the metal oxide CoMn-LDO is generated under high temperature conditions, resulting in a decrease in the number of active sites and catalytic oxidation properties of the catalyst.

Method used

By calcining the kaolin powder at 750°C to 950°C, its crystal structure was destroyed, metakaolin was modified with cationic surfactant, and then Co(Mn)Al-LDH was generated under alkaline hydrothermal conditions, and finally calcined at 650°C to 750°C to prepare a multi-stage structure of silicon-based CoMn-LDO catalyst.

Benefits of technology

This method effectively improves the specific surface area and pore structure of the CoMn-LDO catalyst, maintains the sheet-like multi-stage structure, is not easy to collapse, and significantly improves the catalytic oxidation performance of VOCs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005137880810000011
    Figure HDA0005137880810000011
  • Figure HDA0005137880810000012
    Figure HDA0005137880810000012
  • Figure HDA0005137880810000021
    Figure HDA0005137880810000021
Patent Text Reader

Abstract

The invention belongs to the field of environmental catalytic materials, and particularly discloses a silicon-based CoMn-LDO catalyst of a multilevel structure and a preparation method and application thereof.The preparation method includes the steps that metakaolin is modified through a surfactant and then dispersed into a solution containing cobalt and manganese ions, strong base is added for a hydrothermal reaction, and a product is roasted at high temperature to obtain the CoMn-LDO catalyst. The silicon-based CoMn-LDO catalyst with the multilevel structure is obtained. A cationic surface active agent is adopted for modifying metakaolin, metal ions can be adsorbed and complexed to the surface of the metakaolin, then Co (Mn) Al-LDH of a flexible sheet multi-stage structure is generated under the alkaline hydrothermal condition, meanwhile, the metakaolin can release silicon active ions under the strong alkaline condition, an ion exchange reaction is conducted, and the metal ions are adsorbed and complexed to the surface of the metakaolin. A silicon dioxide framework is formed under roasting and accompanied in a CoMn-LDO crystal, so that the stability of the CoMn-LDO structure is facilitated, a relatively high specific surface area and a relatively high pore structure are kept, and the CoMn-LDO has relatively good catalytic oxidation activity in treatment of VOCs (Volatile Organic Compounds).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a multi-level silicon-based CoMn-LDO catalyst for VOCs treatment and a preparation method thereof, belonging to the field of new environmental catalytic materials. Background Art

[0002] Volatile organic compounds (VOCs) are a common type of pollutants with large emissions and complex composition in industrial production. They can promote the formation of photochemical smog and haze, seriously affect the quality of the atmospheric environment, and endanger human health. With the increasing awareness of environmental protection, the demand for green production is gradually increasing. It is particularly important to adopt efficient and practical technologies to prevent and control VOCs pollution. At present, catalytic oxidation technology has been considered as the most economical and effective means and is widely used in the field of VOCs environmental governance. Compared with precious metal catalysts, non-precious metal catalysts are mainly transition metal oxides (such as: Mn, Ce, Fe, Co, Ni, etc.). They have the advantages of abundant resources, low price, variable valence state and good heat resistance, and have become a research hotspot, but they have disadvantages such as low catalytic activity, high reaction temperature and high operating energy consumption. According to literature reports, reducing the agglomeration of non-precious metal active components by designing the structure and morphology of the catalyst and improving the thermal catalytic oxidation efficiency of VOCs has been considered a common and effective method [Yuxi Liu, Jiguang Deng, Shaohua Xie, Zhiwei Wang, Hongxing Dai. Catalytic removal of volatile organic compounds using ordered porous transition metal oxide and supported noble metal catalysts. Chinese J. Catal., 2016, 37 (8): 1193-1205.]. A Chinese invention patent (application number: 201811642644.5) discloses a Pd-Au core-shell bimetallic supported three-dimensional multi-level structure TiO2 catalyst and its preparation method. The catalyst provided by the invention can completely oxidize benzene at a temperature as low as 175°C. However, the active component in the catalyst is a precious metal, which has the disadvantages of being expensive, scarce in resources, easy to be poisoned, and easy to sinter and deactivate at high temperature. The Chinese invention patent (patent number: ZL201610342743.6) provides a preparation method for synthesizing a Mn-based metal oxide (MnOx) catalyst with a multi-level structure. The technical solution is to first use a dilute H2O2 solution and an inorganic acid solution of KMnO4 to undergo an oxidation-reduction reaction, and then filter, wash, and roast to obtain a rod-shaped and granular multi-level morphological structure MnOx catalyst. However, the active reaction temperature required for a single-component Mn-based non-precious metal oxide catalyst to achieve a toluene conversion rate of 99% is still relatively high. In general, the catalytic activity of a multi-component composite non-precious metal oxide catalyst is better than that of a single-component non-precious metal oxide catalyst, which is mainly attributed to the interactions such as structural or electronic modulation between the components of the composite metal oxide catalyst.The sheet structure of the currently prepared bimetallic LDH will collapse and be destroyed during the high-temperature calcination process, which will lead to a decrease in the number of active sites and catalytic oxidation performance of the catalyst. Summary of the invention

[0003] In view of the problems existing in the background technology, the present invention provides a flaky multi-level structure CoMn-LDO catalyst for VOCs treatment and a preparation method thereof, the purpose of which is to solve the key technical problem that the flaky structure of the layered double metal hydroxide Co(Mn)Al-LDH collapses during the process of generating the metal oxide CoMn-LDO under high temperature conditions, so as to obtain a CoMn-LDO composite material with a flaky multi-level structure. This technology effectively improves the specific surface area and pore structure of the CoMn-LDO catalyst and its catalytic oxidation performance for VOCs.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0005] 1. Calcine kaolin powder at a temperature of 750°C to 950°C for 2 to 4 hours to obtain metakaolin powder. When cooled to 80°C to 100°C, quickly spray a cationic surfactant solution with a mass percentage concentration of 15% to 30% while stirring, wherein the mass ratio of the cationic imidazoline surfactant to the metakaolin is 0.05 to 0.1:1; after spraying, cool to room temperature to obtain surfactant-modified metakaolin; wherein the cationic surfactant is an imidazoline quaternary ammonium salt, such as RX-405 imidazoline quaternary ammonium salt, undecyl hydroxyethyl imidazoline quaternary ammonium salt or heptadecenylamine ethyl imidazoline quaternary ammonium salt.

[0006] 2. Dissolving soluble cobalt salt and soluble manganese salt in deionized water to prepare a mixed solution containing cobalt and manganese ions; wherein the molar concentration of the cobalt salt is 0.1-0.2 mol / L, and the molar ratio of the cobalt salt to the manganese salt is 0.4-0.6:1;

[0007] The soluble cobalt salt described in step 2 is one of cobalt chloride (CoCl2), cobalt sulfate (CoSO4·7H2O), cobalt nitrate (Co(NO3)2·6H2O) or cobalt acetate (CoC4H6O4·4H2O); the soluble manganese salt is one of manganese chloride (MnCl2), manganese sulfate (MnSO4·H2O), manganese nitrate (Mn(NO3)2·4H2O) or manganese acetate (MnC4H6O4·4H2O).

[0008] 3. While stirring, disperse the modified metakaolin powder in step 1 into the mixed solution containing cobalt and manganese ions in step 2, wherein the mass ratio of metakaolin to the mixed solution containing cobalt and manganese ions is 0.02-0.04:1; then dropwise add an alkaline solution with a molar concentration of 2-4 mol / L to adjust the pH value of the system to 9-10, transfer the resulting mixture to a hydrothermal reactor, perform a hydrothermal reaction at a temperature of 110° C. to 140° C. for 6-12 hours, filter and wash until the pH value of the filtrate is 7-7.5, dry and crush the filter cake at a temperature of 80° C. to 90° C., and obtain a CoAl-LDH / MnAl-LDH / SiO2 composite material;

[0009] The alkaline solution described in step 3 is one of sodium hydroxide or potassium hydroxide.

[0010] 4. The CoAl-LDH / MnAl-LDH / SiO2 composite material prepared in step 3 is calcined at a temperature of 650°C to 750°C for 3 to 6 hours to obtain a multi-level silicon-based CoMn-LDO catalyst.

[0011] Beneficial effects of the present invention:

[0012] 1. The present invention heat activates kaolin at high temperature to destroy the crystal structure of kaolin and convert it into an amorphous structure (see attached Figure 1 ), which is beneficial to enhance the reactivity of kaolin.

[0013] 2. The present invention uses a cationic surfactant (imidazoline type) as a template to modify the surface of kaolin, which is conducive to the rapid adsorption, complexation or coordination of metal ions such as Co and Mn to the surface of kaolin, and then a flexible flaky multi-level structure Co(Mn)Al-LDH can be generated under alkaline hydrothermal conditions.

[0014] 3. In the present invention, under the alkaline condition of sodium hydroxide (or potassium hydroxide), metakaolin will release [SiO2(OH)2] 2- 、[SiO(OH)3] - or SiO3 2- These active ions can undergo ion exchange reactions with the anions between the Co(Mn)Al-LDH layers. Then, under high-temperature calcination conditions (i.e., during the transformation of Co(Mn)Al-LDH into CoMn-LDO), the silicon-containing active ions form a stable silica skeleton and are associated with the CoMn-LDO crystals. As a result, during the transformation of Co(Mn)Al-LDH into CoMn-LDO, its flaky multi-level structure will not collapse or be destroyed, which helps to maintain a high specific surface area and pore structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The XRD spectra of kaolin before and after activation. After high-temperature calcination, kaolin is amorphous in composition, mainly silicon dioxide (SiO2).

[0016] Figure 2 XRD spectra of metakaolin, Co(Mn)Al-LDH and CoMn-LDO catalysts prepared in Example 4.

[0017] Figure 3 TEM image of CoMn-LDH prepared in comparative example 1 without kaolin.

[0018] Figure 4 This is a TEM photo of CoMn-LDO after calcination of the sample of Comparative Example 1 (the lamellar structure collapsed and destroyed to form particles).

[0019] Figure 5 This is the TEM photo of CoAl-LDH / MnAl-LDH / SiO2 prepared under kaolin conditions in Example 4.

[0020] Figure 6 for Figure 5 TEM image of CoMn-LDO after calcination (the lamellar structure is not destroyed). DETAILED DESCRIPTION

[0021] The present invention will be further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.

[0022] Example 1

[0023] 1. Calcine 30.0 g of kaolin powder at 750° C. for 4 h to obtain metakaolin powder. When cooled to 80° C., quickly spray 10.0 g of 30% by mass concentration of heptadecaenylamineethylimidazoline quaternary ammonium salt solution while stirring. After spraying, cool to room temperature to obtain imidazoline-type surfactant-modified metakaolin.

[0024] 2. Dissolve 0.6 g of cobalt chloride and 2.1 g of manganese sulfate monohydrate in 50.0 mL of deionized water to prepare a mixed solution containing cobalt and manganese ions;

[0025] 3. While stirring, take 1.0g of modified metakaolin powder and disperse it into 50.0g of a mixed solution containing cobalt and manganese ions; then add a potassium hydroxide solution with a molar concentration of 2.0mol / L to adjust the pH value of the system to 9, transfer the obtained mixture to a hydrothermal reactor, perform a hydrothermal reaction at a temperature of 110°C for 6h, filter and wash until the pH value of the filtrate is 7.5, dry and crush the filter cake at a temperature of 90°C, and obtain a CoAl-LDH / MnAl-LDH / SiO2 composite material;

[0026] 4. The CoAl-LDH / MnAl-LDH / SiO2 composite material prepared in step 3 was calcined at 650°C for 3h to obtain a CoMn-LDO catalyst with a multi-level structure.

[0027] Example 2

[0028] 1. Calcine 30.0 g of kaolin powder at 850° C. for 2 h to obtain metakaolin powder. When cooled to 90° C., quickly spray 10.0 g of 15% mass percent concentration of heptadecaenylamineethylimidazoline quaternary ammonium salt solution while stirring. After spraying, cool to room temperature to obtain imidazoline-type surfactant-modified metakaolin.

[0029] 2. Dissolve 2.8 g of cobalt sulfate heptahydrate and 4.2 g of manganese nitrate tetrahydrate in 50.0 mL of deionized water to prepare a mixed solution containing cobalt and manganese ions;

[0030] 3. While stirring, take 2.0g of modified metakaolin powder and disperse it into 50.0g of a mixed solution of cobalt and manganese ions; then add a sodium hydroxide solution with a molar concentration of 3.0mol / L to adjust the pH value of the system to 9, transfer the obtained mixture to a hydrothermal reactor, perform a hydrothermal reaction at a temperature of 120°C for 12h, filter and wash until the pH value of the filtrate is 7, dry and crush the filter cake at a temperature of 85°C, and obtain a CoAl-LDH / MnAl-LDH / SiO2 composite material;

[0031] 4. The CoAl-LDH / MnAl-LDH / SiO2 composite material prepared in step 3 was calcined at 750°C for 6 hours to obtain a multi-level CoMn-LDO catalyst.

[0032] Example 3

[0033] 1. Calcine 30.0 g of kaolin powder at 950° C. for 3 h to obtain metakaolin powder. When cooled to 100° C., quickly spray 10.0 g of 22.5% mass percent concentration of heptadecaenylamineethylimidazoline quaternary ammonium salt solution while stirring. After spraying, cool to room temperature to obtain imidazoline-type surfactant-modified metakaolin.

[0034] 2. Dissolve 2.2 g of cobalt nitrate hexahydrate and 1.9 g of manganese chloride in 50.0 mL of deionized water to prepare a mixed solution containing cobalt and manganese ions;

[0035] 3. While stirring, take 1.5g of modified metakaolin powder and disperse it into 50.0g of a mixed solution of cobalt and manganese ions; then add a potassium hydroxide solution with a molar concentration of 4.0mol / L to adjust the pH value of the system to 10, transfer the obtained mixture to a hydrothermal reactor, perform a hydrothermal reaction at a temperature of 140°C for 9h, filter and wash until the pH value of the filtrate is 7, dry and crush the filter cake at a temperature of 80°C, and obtain a CoAl-LDH / MnAl-LDH / SiO2 composite material;

[0036] 4. The CoAl-LDH / MnAl-LDH / SiO2 composite material prepared in step 3 was calcined at 700°C for 4 hours to obtain a multi-level CoMn-LDO catalyst.

[0037] Example 4

[0038] 1. Calcine 30.0 g of kaolin powder at 900° C. for 3 h to obtain metakaolin powder. When cooled to 85° C., quickly spray 10.0 g of 20% by mass concentration of heptadecaenylamineethylimidazoline quaternary ammonium salt solution while stirring. After spraying, cool to room temperature to obtain imidazoline-type surfactant-modified metakaolin.

[0039] 2. Dissolve 1.4 g of cobalt nitrate hexahydrate and 2.5 g of manganese nitrate tetrahydrate in 50.0 mL of deionized water to prepare a mixed solution containing cobalt and manganese ions;

[0040] 3. While stirring, take 1.0g of modified metakaolin powder and disperse it in 50.0g of a mixed solution of cobalt and manganese ions; then add a sodium hydroxide solution with a molar concentration of 3.0mol / L to adjust the pH value of the system to 9, transfer the obtained mixture to a hydrothermal reactor, perform a hydrothermal reaction at a temperature of 120°C for 6h, filter and wash until the pH value of the filtrate is 7, dry and crush the filter cake at a temperature of 80°C, and obtain a CoAl-LDH / MnAl-LDH / SiO2 composite material;

[0041] 4. The CoAl-LDH / MnAl-LDH / SiO2 composite material prepared in step 3 was calcined at 700°C for 3h to obtain a multi-level CoMn-LDO catalyst.

[0042] Figure 2 The XRD spectrum of the prepared CoMn-LDO catalyst is shown in FIG. 1 . Among them, the metakaolin has SiO2-specific diffraction peaks at 2θ of 20.8° and 26.6° (JCPDS PDF#97-003-9830). The product of step 3 of Example 4, CoAl-LDH / MnAl-LDH / SiO2 composite material (Example 4 (before calcination)), shows that the CoAl-LDH-specific diffraction peaks appear at 2θ of 11.5° and 23.5° (JCPDS PDF#51-0045), and the MnAl-LDH-specific diffraction peaks appear at 2θ of 11.7°, 23.5°, 32.6°, 34.5°, and 58.1° (JCPDS PDF#51-1529), indicating that CoAl-LDH / MnAl-LDH / SiO2 mainly exists in the form of a mixture of CoAl-LDH and MnAl-LDH. It can be seen from Example 4 that by comparing the PDF cards of Co3O4 and MnCo2O4, it is known that the diffraction peaks specific to Co3O4 appear at 2θ of 31.2°, 36.8°, 44.8°, 59.3°, and 65.2° (JCPDS PDF#09-0418), and the diffraction peaks specific to MnCo2O4 appear at 2θ of 30.5°, 35.9°, and 63.8° (JCPDS PDF#23-1237), indicating that the CoMn-LDO catalyst mainly exists in the form of Co3O4 and MnCo2O4.

[0043] Comparative Example 1

[0044] In Comparative Example 1, step 1 of Example 4 is deleted, and other processes remain unchanged. The specific steps are as follows:

[0045] 1. Dissolve 1.4 g of cobalt nitrate hexahydrate and 2.5 g of manganese nitrate tetrahydrate in 50.0 mL of deionized water to prepare a mixed solution containing cobalt and manganese ions;

[0046] 2. Take 50.0g of the mixed solution of cobalt and manganese ions, add a sodium hydroxide solution with a molar concentration of 3.0 mol / L while stirring to adjust the pH value of the system to 9, transfer the obtained mixture to a hydrothermal reactor, perform hydrothermal reaction at a temperature of 120°C for 6h, filter and wash until the pH value of the filtrate is 7, dry and crush the filter cake at a temperature of 80°C, and obtain a CoMn-LDH flake material;

[0047] 3. The CoMn-LDH flake material prepared in step 2 is calcined at 700° C. for 3 h to obtain a CoMn-LDO catalyst.

[0048] In Comparative Example 1, the CoMn-LDH prepared in the absence of kaolin, after calcination, the CoMn-LDO layer structure collapsed and destroyed to form particles.

[0049] Comparative Example 2

[0050] In Comparative Example 2, the "imidazoline quaternary ammonium salt modification process" in step 1 of Example 4 is deleted, and other processes remain unchanged. The specific steps are as follows:

[0051] 1. Calcine 30.0 g of kaolin powder at 900 ° C for 3 h and cool it to 85 ° C to obtain metakaolin powder;

[0052] 2. Dissolve 1.4 g of cobalt nitrate hexahydrate and 2.5 g of manganese nitrate tetrahydrate in 50.0 mL of deionized water to prepare a mixed solution containing cobalt and manganese ions;

[0053] 3. While stirring, take 1.0g of metakaolin powder and disperse it in 50.0g of a mixed solution of cobalt and manganese ions; then add a sodium hydroxide solution with a molar concentration of 3.0mol / L to adjust the pH value of the system to 9, transfer the obtained mixture to a hydrothermal reactor, perform a hydrothermal reaction at a temperature of 120°C for 6h, filter and wash until the pH value of the filtrate is 7, dry and crush the filter cake at a temperature of 80°C, and obtain a Co(Mn)Al-LDH / SiO2 composite material;

[0054] 4. The CoAl-LDH / MnAl-LDH / SiO2 composite material prepared in step 3 was calcined at 700°C for 3h to obtain a CoMn-LDO catalyst.

[0055] Comparative Example 3

[0056] In Comparative Example 3, the "sodium hydroxide" in step 3 of Example 4 is replaced with "aqueous ammonia", and the other processes remain unchanged. The specific steps are as follows:

[0057] 1. Calcine 30.0 g of kaolin powder at 900° C. for 3 h to obtain metakaolin powder. When cooled to 85° C., quickly spray 10.0 g of 20% by mass concentration of heptadecaenylamineethylimidazoline quaternary ammonium salt solution while stirring. After spraying, cool to room temperature to obtain imidazoline-type surfactant-modified metakaolin.

[0058] 2. Dissolve 1.4 g of cobalt nitrate hexahydrate and 2.5 g of manganese nitrate tetrahydrate in 50.0 mL of deionized water to prepare a mixed solution containing cobalt and manganese ions;

[0059] 3. While stirring, take 1.0g of modified metakaolin powder and disperse it in 50.0g of a mixed solution of cobalt and manganese ions; then add ammonia water with a molar concentration of 3.0mol / L to adjust the pH value of the system to 9, transfer the obtained mixture to a hydrothermal reactor, perform hydrothermal reaction at a temperature of 120°C for 6h, filter and wash until the pH value of the filtrate is 7, dry and crush the filter cake at a temperature of 80°C, and obtain a Co(Mn)Al-LDH / metakaolin composite material;

[0060] 4. The CoMn-LDH / metakaolin composite material prepared in step 3 was calcined at 700° C. for 3 h to obtain a CoMn-LDO catalyst.

[0061] Performance Evaluation

[0062] Catalytic oxidation performance test: The catalyst samples in the present invention were evaluated for catalytic oxidation performance using toluene as a simulated gas. The activity evaluation of the catalyst was carried out on a VOC adsorption and desorption catalytic reactor (VDRT-3000, Quzhou Ward Instrument Co., Ltd.). The catalyst sample powder prepared by the present invention was tableted and granulated on an infrared tablet press 1g (40-60 mesh), then mixed evenly with 4g of quartz sand, and placed on quartz wool in a quartz tube with an inner diameter of 30mm. The toluene simulated gas was generated by bubbling toluene solvent with nitrogen at room temperature, and high-purity air was used as a carrier gas. The toluene concentration was controlled by adjusting the flow rates of the bubbling gas and the carrier gas, that is: the air flow rate was 270mL / min, and the nitrogen flow rate was 30mL / min, so that the toluene concentration was 1700mg / m 3 The concentration of toluene was analyzed online by GC-2014 gas chromatograph. The temperature (T 99 ) was used to evaluate the performance of the catalyst, and the results are shown in Table 1. 99 The lower the temperature, the higher the activity of the catalyst and the better the catalytic oxidation performance. As can be seen from Table 1, the CoMn-LDO catalyst prepared in the present invention has a higher specific surface area and a lower temperature catalytic oxidation activity.

[0063] Table 1

[0064] name <![CDATA[T 99 / ℃]]> <![CDATA[Specific surface area of Co(Mn)Al-LDH / m 2 ·g -1 > <![CDATA[Specific surface area of CoMn-LDO / m 2 ·g -1 > Example 1 273 153 148 Example 2 277 155 150 Example 3 271 152 146 Example 4 270 159 152 Comparative Example 1 310 121 64 Comparative Example 2 294 128 110 Comparative Example 3 305 122 85

[0065] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a multi-level silicon-based CoMn-LDO catalyst, characterized in that: (1) calcining kaolin powder to obtain metakaolin powder, and modifying the metakaolin powder with a surfactant to obtain modified metakaolin powder; (2) dissolving a soluble cobalt salt and a soluble manganese salt in deionized water to prepare a mixed solution containing cobalt and manganese ions; (3) dispersing the modified metakaolin powder in step (1) into the mixed solution containing cobalt and manganese ions in step (2), then dropping a strong alkaline solution until the pH value of the system is 9 to 10, transferring the resulting mixture to a hydrothermal reactor for reaction, filtering, washing, drying and crushing the filter cake to obtain a CoAl-LDH / MnAl-LDH / SiO2 composite material; (4) calcining the CoAl-LDH / MnAl-LDH / SiO2 composite material obtained in step (3) at a temperature of 650°C to 750°C to obtain a silicon-based CoMn-LDO catalyst with a multi-level structure.

2. The method for preparing the multi-level silicon-based CoMn-LDO catalyst according to claim 1, characterized in that: The surfactant is a cationic surfactant, and the mass ratio of the cationic surfactant to the metakaolin is 0.05-0.1:

1.

3. The method for preparing the multi-level silicon-based CoMn-LDO catalyst according to claim 1, characterized in that: The molar ratio of cobalt salt to manganese salt in the mixed solution containing cobalt and manganese ions is 0.4-0.6:1; the molar concentration of the cobalt salt is 0.1-0.2 mol / L.

4. The method for preparing the multi-level silicon-based CoMn-LDO catalyst according to claim 1, characterized in that: The soluble cobalt salt is one of cobalt chloride, cobalt sulfate, cobalt nitrate or cobalt acetate; the soluble manganese salt is one of manganese chloride, manganese sulfate, manganese nitrate or manganese acetate.

5. The method for preparing the multi-level silicon-based CoMn-LDO catalyst according to claim 1, characterized in that: In step (3), the mass ratio of the modified metakaolin powder to the mixed solution containing cobalt and manganese ions is 0.02 to 0.04:

1.

6. The method for preparing the multi-level silicon-based CoMn-LDO catalyst according to claim 1, characterized in that: In step (3), the strong alkaline solution is one of a sodium hydroxide solution or a potassium hydroxide solution.

7. The method for preparing the multi-level silicon-based CoMn-LDO catalyst according to claim 1, characterized in that: In step (3), the temperature of the hydrothermal reaction is 110° C. to 140° C., and the hydrothermal reaction time is 6 to 12 hours.

8. A multi-level silicon-based CoMn-LDO catalyst prepared according to the method of any one of claims 1 to 7.

9. Use of the multi-level silicon-based CoMn-LDO catalyst according to claim 8 in catalytic oxidation of VOCs.

Citation Information

Patent Citations

  • Preparation of Mn-based Metal Oxide Catalysts by Rapid Reduction of H2O2 and Its Application in Low Temperature Catalytic Combustion of VOCs

    CN105921146B

  • Supported metal catalyst, preparation method thereof, and VOCs processing method

    CN109647386A